Vertical distributions of organic matter components in sea ice near Cambridge Bay, Dease Strait, Canadian Archipelago - Kim, Kwanwoo; Ha, Sun-Yong; Shin, Kyung-Hoon; Kim, Jee-Hoon; Mundy, C. J.; Dalman, Laura A.; Kim, Bo Kyung; Lee, Dabin; Jang, Hyo Keun; Kim, Yejin; Park, Sanghoon; Lee, Sang Heon (Frontiers in Marine Science, 2023)
The vertical characteristics of organic matter within the sea ice were investigated, specifically focusing on chlorophyll a (Chl-a), particulate organic carbon and nitrogen (POC and PON), carbohydrates (CHO), proteins (PRT), lipids (LIP), and food material (FM). The analysis was conducted on sSamples were takencollected from the bottom, middle, and top sections of the sea ice column near Cambridge Bay during the spring of 2018. Based on the δ 13 C signature, biochemical composition, and POC contribution of biopolymeric carbon (BPC), the origin of the organic substances within the sea ice waswere considered to be mainlypredominantly fromattributed to marine autotrophs. While Tthe highest concentrations of each parameter were observed at the sea ice bottom, but the notable concentrations were also found atin the upper sections were considerably high. The average sea ice column-integrated Chl-a concentration was 5.05 ± 2.26 mg m −2 , with and their contribution of the bottom ice section wascontributing 59% (S.D. = ± 10%) to the total integration. The column-integrated concentrations forof FM, BPC, POC, and PON were 2.05 ± 0.39, 1.10 ± 0.20, 1.47 ± 0.25, and 0.09 ± 0.03 g m −2 , respectively. The cContributions of the bottom ice section to these column-integrated concentrations varied for each parameter, with values of 20 ± 6, 21 ± 7, 19 ± 5, and 28 ± 7%, respectively. While Tthe bottom ice section exhibited higha substantial Chl-a contribution of the bottom ice section in this study alignes with previous findings.studies Conversely, significantly higher contributions of the other parameters were found observed in the upper sea ice sections. This impliessuggests that significant the particulate matter within the interior of the sea ice could potentially serve as an additional food source for upperhigher trophic grazers or act as a seedsing material for a the phytoplankton bloom during the ice melting season.TheOur findings study highlights the importance of comprehensivefurther intensive field measurements encompassing the entire sea ice section to better estimateunderstand the distribution of organic carbon pools within the sea ice in the Arctic Ocean.